Clinical outcome prediction from mean platelet volume in patients undergoing percutaneous coronary intervention in Korean cohort: Implications of more simple and useful test than platelet function testing. (August 2014) - Choi, Seo-Won; Choi, Dong-Hyun; Kim, Hyun-Wook; Ku, Yo-Han; Ha, Sung-Il; Park, Geon
Abstract The aim of this study was to determine the associations of the mean platelet volume (MPV) with the development of adverse outcomes after percutaneous coronary intervention (PCI) and platelet reactivity. MPV and platelet function testing were analysed in 208 patients who underwent PCI. The primary endpoint was cardiac death. The secondary endpoint analysed was cardiovascular events (CVE): the composite of myocardial infarction (MI), target vessel revascularization (TVR), and stent thrombosis (ST). The median MPV level, aspirin reaction unit (ARU), P2Y12 reaction units (PRU) and P2Y12% inhibition (PI%) of clopidogrel were 8.55 (IQR 8.00–9.18) fl, 401.0 (IQR 389.3–442.0) ARU, 222.0 (IQR 169.0–272.3) PRU and 22 (IQR 9–38) %, respectively. We observed that high values of MPV were associated with elevated ARU (r = 0.165, p = 0.017) and decreased PI% (r = −0.167, p = 0.016). There were 10 events of cardiac death, 3 MI (including 1 event of ST), and 8 TVR during a mean of 7.6 months of follow-up. The Kaplan–Meier analysis revealed that the higher MPV group (≥8.55 fl, median) had a significantly higher cardiac death rate compared to the lower MPV group (<8.55 fl) (7.7% vs. 1.9%, log-rank: p = 0.035). However, aspirin or clopidogrel resistance (>550 ARU, <40 PI%, respectively) did not predict cardiac death. When the MPV cut-off level was set to 8.55 fl using the receiver operating characteristic curve, the sensitivity was 80% and the specificity was 51.5% for differentiating between the group with cardiac death and the group without cardiac death. This value was more useful in patients with clinical diagnosis of acute coronary syndrome (ACS). Furthermore, ACS patients with an MPV over 8.55 fl had high cardiac death and CVE risk without atorvastatin loading before PCI (Log-Rank = 0.0031, 0.0023, respectively). The results of this study show that MPV was a predictive marker for cardiac death after PCI; its predictive power for cardiac death was more useful in patients with ACS.